2021
DOI: 10.2147/ijgm.s322726
|View full text |Cite
|
Sign up to set email alerts
|

Variant of TSHR is Not a Frequent Cause of Congenital Hypothyroidism in Chinese Han Patients

Abstract: Purpose To screen variants of the thyroid stimulating hormone receptor ( TSHR ) gene among congenital hypothyroidism (CH) patients. Patients and Methods We conducted a genetic screening of the TSHR gene in a cohort of 125 Chinese CH patients. Variants were detected by customized targeted next-generation sequencing. Results A total of 11 TSHR missense heterozygous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…TSHR is another gene with a high prevalence of germline P/LP variants. A study showed that TSHR p.F525S was the most prevalent variant in a Chinese congenital hypothyroidism [ 62 ]. This variant also had a relatively high odds ratio in our case–control analysis.…”
Section: Discussionmentioning
confidence: 99%
“…TSHR is another gene with a high prevalence of germline P/LP variants. A study showed that TSHR p.F525S was the most prevalent variant in a Chinese congenital hypothyroidism [ 62 ]. This variant also had a relatively high odds ratio in our case–control analysis.…”
Section: Discussionmentioning
confidence: 99%